THE COMPARISON OF PRESSURE CONTROLLED VENTILATION AND VOLUME CONTROLLED VENTILATION ON OPERATION DURING GENERAL ANESTHESIA WITH THE USE OF MECHANICAL VENTILATION PEVENT NARAYA - Nurjannah Achmad; Arief Kurniawan; Sutrisno Sutrisno; Siska Telly Pratiwi; Nur Pudyastuti Pratiwi (Journal of Innovation Research and Knowledge, 2023)
In general, surgery is performed under the influence of anesthesia, and among others is conducted with general anesthesia. Ventilation Control pressure (PCV) and Volume Control Ventilation (VCV) are modes available Ventilator techniques in the perioperative period. This research compared ventilators perioperative and blood gas variable of the volume-controlled ventilation (VCV) and the ventilation pressure controlled (PCV) in patients undergoing surgery under general anesthesia. After obtaining the approval from the Institutional Ethics Committee and informed consent, sixty patients scheduled for surgery conducted in supine position under general anesthetics were randomly allocated into two groups to receive the VCV or PCV modes with Randomized Controlled Trial (RCT) method. Group V (30 patients) received VCV and Group P (30 patients) received PCV. The main objective was for variable oxygenation FiO2, systolic and diastolic blood pressure, average arterial pressure, pulse rate at different times point, namely T0-12 minutes before induction, T1-12 minutes before induction intubate, T2-12 minutes after intubation and so forth in every 15 minutes until the surgery was complete. The Secondary goals included sedation scale parameter and vomiting scale after extubation. Paired samples t test for overall comparisons and Ramsay scores for sedation and vomiting scales. The main variable and secondary variable were align in the two groups (P>0.05). In clinical, both PCV and VCV groups were suitable for ventilator technique on patients with general anesthesia surgery.